PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DAN MANAJEMEN KELAS UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SEKOLAH DASAR - Kencono, Melati Retno; Sanoto, Herry; Azizah, Nurul (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to improve mathematics learning outcomes. The subjects of this research were fourth-grade students at SD Negeri Kecandran 01 Salatiga. Initial survey results showed an average mathematics learning score of 52.6. To address this issue, the Problem-Based Learning model and classroom management strategies were implemented to enhance students' mathematics performance. This study employed Classroom Action Research (CAR) using Ernest T. Stringer’s model, which consists of the stages: look, think, and act. Data collection instruments included interviews, observations, documentation, and tests. The study utilized both quantitative and qualitative descriptive analysis techniques. The research results showed an increase in the average score from 52.2 in the pre-cycle to 67.8 in cycle I, and further improvement to 81.1 in cycle II. Therefore, it can be concluded that the Problem-Based Learning model combined with effective classroom management is effective in improving mathematics learning outcomes for fourth-grade elementary students.